Photograph of Nurse Cuong Phu Pham in Front of Door - Pham, Cuong Phu::::::::: (2020)
Photograph of nurse and nursing instructor Cuong Phu Pham taken at place of work during the COVID-19 Pandemic and Nurse Week 2020.